Perbandingan Temuan Anatomi Mastoid Tipe Pneumatik dan Diploik Hasil Diseksi Tulang Temporal Peserta Didik Program Studi Ilmu Kesehatan THT-BKL - Wahyu Widiantari, I Gusti Ayu Putu; Eka Putra Setiawan; Komang Andi Dwi Saputra; I Gde Ardika Nuaba; Rahayu, Made Lely (PERHATI-KL, 2025)
Background: Simple mastoidectomy is the most common approach to managing chronic suppurative otitis media (CSOM). This procedure aims to partially or completely remove mastoid cells, to overcome the infection in the middle ear. However, the mastoid bone pneumatization type may influence the result of simple mastoidectomy or temporal bone dissection. Purpose: To determine the difference in the anatomical findings of pneumatic and diploic mastoid types in the temporal bone dissections. Method: This cross-sectional study assesed on pneumatic and diploic types of mastoid bone, on temporal bone dissections findings. The mastoid bones used in this study were temporal bone of the Indonesian cadavers. Data were obtained from direct observation of the number of anatomical landmarks found during temporal bone dissections on each type of mastoid bone; and the maximal anatomical landmark found in each bone was seven. The number of anatomical landmarks between pneumatic and diploic mastoid bone was compared using the Mann-Whitney U test. Result: The mean of overall anatomical landmarks found during temporal bone dissection was 4.50±1.70. No significant difference in the number of anatomical landmarks was found between pneumatic and diploic mastoid bone (4.57±0.79 vs. 4.43±0.53; p=0.827). Conclusion: There was no significant difference in anatomical findings between pneumatic and diploic mastoid bone in temporal bone dissections. Broad knowledge is vital for successful mastoidectomy in all types of mastoid bone.